Pelatihan Membuat Sabun Cuci Piring: Upaya Membangun Ekonomi Jemaat - Blegur, Romelus; Siregar, Esron Mangatas; Karo, Dinar Br; Gea, Leniwan Darmawati; Mbinu, Eni Loda (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
Economic pressures require hard work to overcome them. This can be done through innovation and creativity to find job opportunities that can be economically profitable, but also useful for society, especially in the context of church congregations. Related to that, one important effort is training to make useful dishwashing soap, but also a business opportunity in relation to the need for the use of dishwashing soap in society. Based on that, STT ATI carries out training activities to make dishwashing soap to equip lecturers and students to answer the needs of the church. The methods used in this training are presentations, tutorials and practice. The results of this activity are that the participants understand the material presented, and gain direct experience in the practice of making dishwashing soap. In addition, the participants gain benefits and economic advantages from the activity.